COVID-19 Bereavement in Ten Latin American Countries: Measurement Invariance of the Pandemic Grief Scale and Its Relation to Suicidal Ideation (2023)
The present study aimed to evaluate the cross-cultural measurement invariance of the Pandemic Grief Scale (PGS) in ten Latin American countries. A total of 2,321 people who had lost a family member or other loved one due to COVID-19 participated, with a mean age of 34.22 years old (SD = 11.99). In addition to the PGS, a single item of suicidal ideation was applied. The unidimensional model of the PGS had adequate fit in most countries and good reliability estimates. There was evidence of measurement invariance by country and gender. Also, a one-point increase in the PGS was associated with an almost twofold increase in the odds of suicidal ideation. Scores greater than or equal to 4 on the PGS are proposed as a cut off to identify individuals with suicidal ideation. Strong evidence of the cross-cultural validity of the PGS is provided.